IMPLEMENTASI PROGRAM KELAS INKLUSIF PADA PERGURUAN TINGGI KEISLAMAN DI SURAKARTA - Umam, Robith Khoiril; Krisnawati, Ristiya (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
This research aimed at describing the implementation of inclusive class program at Islamic higher education in Surakarta, revealing supporting and constraining factors of program implementation, and describing the understanding, attitude, and efforts of the lecturers in inclusive class. This is descriptive qualitative research. The research subjects were lecturers and students in inclusive class program. Data collection techniques are observation, interviews, and documentation. The data analysis technique used the model developed by Miles and Hubermann (2014) consisting of data reduction, data display and drawing conclusion. The results of this research indicate that the implementation of the inclusive class program has not been running perfectly, proven with the finding of several fundamental constraints becoming obstacles to the implementation of the program. Furthermore, several supporting factors to the program implementation were also found which could be used as the main foundation to improve the implementation. Furthermore, the understanding, attitude, and efforts of the lecturers regarding to the implementation of the inclusive class are very positive, as proven by the awareness and understanding regarding improving services for students with special needs. Several attempts were made to carry out the program properly by planning for the physical environment, teaching procedures, and learning materials using adaptive tools. Keywords: program implementation, inclusive class, Islamic higher education